Pathological Investigations of Intracranial Atherosclerosis Using Multiple Hypercholesterolemic Rabbit Models - Tang, Xiangming; Niimi, Manabu; Zhou, Huanjin; Chen, Lu; Chen, Yajie; Yan, Haizhao; Shiomi, Masashi; Fan, Jianglin (Frontiers in Endocrinology, 2022)
Background: Intracranial atherosclerosis (ICAS) is one of the most common causes of ischemic stroke, but there are few animal models that can recapitulate its pathological features. In this study, we examined whether it is possible to study ICAS using three types of hyperlipidemic rabbit models that exhibit different lipoprotein profiles. Materials and Methods: We examined Watanabe heritable hyperlipidemic (WHHL) rabbits, apoE knockout (KO) rabbits and wild-type rabbits (WT) fed a cholesterol diet, in addition to WT rabbits fed a standard diet as a control. The whole brain was dissected and embedded in paraffin. Serial sections were stained with either hematoxylin/eosin or elastica van Gieson, or immunohistochemically stained with monoclonal antibodies against macrophages and smooth muscle cells. We investigated (1) the presence of cerebral atherosclerosis; (2) the lesion locations in the cerebral arteries; (3) the degree of lumen stenosis; (4) pathological features and cellular components of the lesions in these rabbits; and (5) whether hypertension affects ICAS. Results: ICAS was detected in apoE and WHHL rabbits, but not in WT rabbits. Compared with apoE KO rabbits, WHHL rabbits had greater ICAS. The lesions of cerebral atherosclerosis were mainly distributed at the bifurcations of the posterior cerebral artery, basilar artery and vertebral artery, and they were basically characterized by smooth muscle cells and extracellular matrix with few macrophages. The extent of the ICAS in WHHL rabbits was significantly increased by hypertension. Conclusions: ICAS was detected in WHHL and apoE KO rabbits, and occurred in specific locations in the cerebral arteries. Hypertension promotes the development of ICAS in the setting of hypercholesterolemia.